2020
DOI: 10.21203/rs.3.rs-127636/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sickle Cell Disease (SCD) and COVID-19 – A Case Series

Abstract: The ongoing pandemic of COVID-19 that started in the Hubei province of China in late December 2019, caused by severe acute respiratory syndrome corona virus-2 (SARS CoV-2). Globally millions affected by the disease so far. The risk of COVID-19 severity and its complications increases with age and other comorbidities. The course of SARS-CoV-2 infection or its related complications has yet to be established in patients with sickle cell disease (SCD), once more evidence is available. It is clear from the availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“… n/a 0 (0) Allison et al [ 69 ] USA 1 (1/0) 27 HbSC (1) BT (1) Early red blood cell exchange treatment may have helped mitigate COVID-19 pneumonia and ACS. n/a 0 (0) Al-Naami et al [ 42 ] Saudi Arabia 3 (2/1) 25 HbSS (3) HU (1) Disease course was mild to moderate w/o complications or death. 2 (67) 0 (0) Al-Naami et al [ 106 ] Saudi Arabia 1 (1/0) 29 HbSS/Sβ 0 HU (1) Pt presented asymptomatic with h/o sore throat and loose motions; Uneventful recovery.…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… n/a 0 (0) Allison et al [ 69 ] USA 1 (1/0) 27 HbSC (1) BT (1) Early red blood cell exchange treatment may have helped mitigate COVID-19 pneumonia and ACS. n/a 0 (0) Al-Naami et al [ 42 ] Saudi Arabia 3 (2/1) 25 HbSS (3) HU (1) Disease course was mild to moderate w/o complications or death. 2 (67) 0 (0) Al-Naami et al [ 106 ] Saudi Arabia 1 (1/0) 29 HbSS/Sβ 0 HU (1) Pt presented asymptomatic with h/o sore throat and loose motions; Uneventful recovery.…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
“…Case studies show even higher hospitalization trends, although this may be in part due to patient selection bias. Of the 9 case studies that reported both hospitalized and non-hospitalized patients, the COVID-19-related hospitalization rate for persons with SCD was 72% (44/61) [ [42] , [43] , [44] , [45] , [46] ].…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%